A remarkable colorimetric probe for fluorescent ratiometric and ON-OFF discriminative detection of Hg2+ and Cu2+ by double-channel imaging in living cells. (December 2019) - Shi, Wen-Jing; Li, Chun-Feng; Huang, Yan; Tan, Hui-ya; Wei, Yong-Feng; Liu, Fenggang; Feng, Liu-Xia; Zheng, Liyao; Chen, Guo-Shu; Yan, Jin-wu
Abstract: A novel click-derived monostyryl BODIPY-based fluorescent probe has been prepared. Notably, upon exposure to Hg 2+ or Cu 2+, it exhibited remarkable blue-shifted absorptions from 592 to either 555 for Hg 2+ or 502 nm for Cu 2+ with distinct color changes from blue to purple for Hg 2+ or yellow for Cu 2+ in CH3 CN/H2 O. Interestingly, its fluorescence showed significant ratiometric (Hg 2+ ) and ON-OFF (Cu 2+ ) changes. Notably, the probe displayed ratiometric fluorescence from 690 to 602 nm with a 65-fold enhancement in fluorescence ratio of I602 /I690 for Hg 2+ and underwent a substantial ON-OFF fluorescence for Cu 2+ . Furthermore, this probe was successfully used in Hela cells and could easily discriminate Hg 2+ and Cu 2+ through double-channel imaging. These overall results illustrate that this monostyryl BODIPY potentially serves as a remarkable colorimetric probe for fluorescent ratiometric and ON-OFF discriminative detection of Hg 2+ and Cu 2+ in solutions and living cells by a remarkable double-channel change. Graphical abstract: Image 1 Highlights: A novel monostyryl BODIPY-based probe was prepared through click reaction. Colorimetric changes from blue to purple for Hg 2+ or yellow for Cu 2+ were easily seen. It showed large ratiometric for Hg 2+ and ON-OFF for Cu 2+ fluorescence. It successfully distinguished Hg 2+ and Cu 2+ in living cells by double-channel imaging. A 37-fold enhanced ratio for Hg 2+ and a sufficient quenching for Cu 2+ were seen in cells.